Homozygous missense variants in NTNG2, encoding a presynaptic netrin-G2 adhesion protein, lead to a distinct neurodevelopmental disorder - Dias, CM; Punetha, J; Zheng, C; Mazaheri, N; Rad, A; Efthymiou, S; Petersen, A; Dehghani, M; Pehlivan, D; Partlow, JN; Posey, JE; Salpietro, V; et al. (Elsevier, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.